2013
DOI: 10.3109/21678421.2013.852589
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord atrophy correlates with disease duration and severity in amyotrophic lateral sclerosis

Abstract: Our objective was to investigate spinal cord (SC) atrophy in amyotrophic lateral sclerosis (ALS) patients, and to determine whether it correlates with clinical parameters. Forty-three patients with ALS (25 males) and 43 age- and gender-matched healthy controls underwent MRI on a 3T scanner. We used T1-weighted 3D images covering the whole brain and the cervical SC to estimate cervical SC area and eccentricity at C2/C3 level using validated software (SpineSeg). Disease severity was quantified with the ALSFRS-R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 17 publications
3
43
1
Order By: Relevance
“…Interestingly, the same pattern of atrophy and flattening was recently reported in a cohort of patients with Friedreich's ataxia, which is known to harbor severe (but relatively restricted) damage to the posterior funiculi [14]. In contrast, degenerative diseases with lateral column involvement (e.g., amyotrophic lateral sclerosis) have atrophy, but no significant flattening [15]. Taken together, these data indicate that spinal damage in SCA3 resembles that found in Friedreich's ataxia with predominant damage to posterior rather than lateral columns.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, the same pattern of atrophy and flattening was recently reported in a cohort of patients with Friedreich's ataxia, which is known to harbor severe (but relatively restricted) damage to the posterior funiculi [14]. In contrast, degenerative diseases with lateral column involvement (e.g., amyotrophic lateral sclerosis) have atrophy, but no significant flattening [15]. Taken together, these data indicate that spinal damage in SCA3 resembles that found in Friedreich's ataxia with predominant damage to posterior rather than lateral columns.…”
Section: Discussionmentioning
confidence: 57%
“…High-field MRI scanners and novel postprocessing techniques now enable reliable quantification of spinal cord morphometry [13][14][15][16]. Such analyses have proven useful to investigate similar diseases such as Friedreich's ataxia and Amyotrophic lateral sclerosis, but were not yet fully explored in SCA3 [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…35 The precise molecular mechanisms underlying C9orf72-associated degeneration remains largely unknown, even if putative cell-to-cell propagation of the DPRs and TDP-43 inclusions has been proposed. 36 Despite the detection sensitivity of novel spinal imaging techniques in ALS, [24][25][26][37][38][39] the lack of imaging findings in younger mutation carriers may be due to technological limitations and does not necessarily represent lack of pathology. Presymptomatic imaging in C9orf72 has dual academic and clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Most neuroimaging studies in ALS have been conducted in the brain and show evidence of GM and WM degeneration . The few studies conducted so far in the cervical SC have reported a reduction in cord CSA, but have not investigated GM/WM separately, probably because of insufficient GM/WM image contrast and low spatial resolution. In this study, thanks to the high GM/WM contrast and the higher resolution of our T 2 *‐weighted images, we were able not only to confirm atrophy of the cervical SC, but also to quantify atrophy occurring in both GM and WM .…”
Section: Discussionmentioning
confidence: 99%